Antibiotic resistance pattern of Escherichia coli isolated from patients with urinary tract infection - Taseen, Arifa (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2019.